Analisis Profil Behavior, Attention, Language, Stimming (BALS) pada Anak Gangguan Spektrum Autisme (Studi Kasus AF yang Pernah Menjalani Diet CFGF di SLB Negeri 1 Lubuk Sikaping) - Mukhlis, Fairuz Syifa; Rahmahtrisilvia, Rahmahtrisilvia; Mahdi, Arisul; Handayani, Endang Sri; Tsaputra, Antoni (Indo-MathEdu Intellectuals Journal, 2025)
Children with Autism Spectrum Disorder (ASD) are children who experience complex challenges, characterized by symptoms in social communication, repetitive behaviors, and limited interests. This study discusses a case study of AF, who had previously undergone a GFCF diet at SLB Negeri 1 Lubuk Sikaping. The purpose of this study is to describe the characteristics of Behavior, Attention, Language, Stimming (BALS) that appear in ASD children in grade XI at SLB Negeri 1 Lubuk Sikaping. This qualitative research uses a case study approach, which primarily focuses on a single case or multiple cases studied in real life. The subject of this study is a child with autism spectrum disorder, initials AF. The data collection techniques used in this study are observation and interviews. The data analysis technique involves several stages, namely data reduction, data presentation, and drawing conclusions. The results of this study show that behavior depends on environmental conditions and the activities provided. Attention AF is able to maintain focus for a limited period of time. Language responds to name calls, understands commands, and uses verbal and nonverbal communication fairly well. Meanwhile, stimming behavior tends to be consistent every day, although its intensity can be influenced by emotional and environmental conditions